Simulation study of the effects of out-of-phase synchronizing currents on power system components - Lim, Jun Liang. (2011)
Today, power quality problem is one of the important issues in power systems. One of the most significant issues regarding power quality is voltage sag which reduces the voltage amplitude for a short time. Voltage sags are disturbances that are arise by faults (short-circuit), energising power transformers, starting electrical motors and sudden changes of loads. Faults causes voltage sag in the distribution networks and varies loads connected with time are different. Uninterruptible Power Supplies (UPS) is often connected to the distribution network providing an uninterruptible source for the essential identified power equipments. It serves to prevent undesired features of the power source (outages, sags, surges, bad harmonics, etc.) adversely affecting the performance of connected loads. Alternating Current (AC) induction motors are the most common motors used in industrial motor control systems. It consists of windings, which create a rotating magnetic field and rotor conductors continuously cut which in turn induces a high current. The induced current is usually very high at the initial start up which hence causes voltage dips. Different types of starting method had been employed on different types of induction motors which allow in the reduction of heavy starting currents. In this Thesis, PSCAD is greatly applied for the project. Unsymmetrical fault which is common to appear in the Distributed Network is simulated and analysed. The analysis work includes modelling the Distribution Network with protective devices and simulating the phase-to-ground fault which commonly pose to occur. Uninterruptible Power Supplies (UPS) which is commonly connected in the distribution network is constructed to enhance the simulation study. To prepare for an induction motor which is commonly connected to the distribution network, induction motor starter is hence introduced to reduce the motor heavy starting current.